Potassium silicate to control Oebalus insularis Stål in rice in Quevedo, Ecuador - Llerena-Ramos, Luis Tarquino; Rodríguez-Rodríguez, Sergio; Reyes-Pérez, Juan José; Jiménez-Pizarro, María; López-Álvarez, Sandra; Rueda-Puente, Edgar Omar (Revista Mexicana de Ciencias Agrícolas, 2025)
Oebalus insularis Stål, colloquially known as the rice stink bug, causes damage to rice crops, the production losses of which can range between 30 and 65%, which is why agroecological alternatives for its control without the application of polluting synthetic chemicals are increasing. The research aimed to assess the use of beneficial microorganisms and compost with silicon for the control of O. insularis Stål, in Oryza sativa L., cultivar INIAP-14. The research was conducted in the summer-autumn 2023 in Quevedo, Ecuador, under field conditions in a clay loam soil, using six treatments consisting of a control without any application (T1), Buffago insecticide at 0.5 L ha-1 (T2); Azotobacter chroococcum, strain Ag, at 1 x 109 CFU ml-1 (T3); liquid compost with potassium silicate (K4SiO4) at 5 L ha-1 (T4); Metarhizium anisopliae, strain 45, at 1.2 L ha-1 (T5), and a combined treatment with A. chroococcum, liquid compost with potassium silicate, and M. anisopliae (T6), in a completely randomized design. The dependent variable evaluated was the number of insects per plot before and after applying the treatments. The results show a significant variation in the insect population before and after applying the treatments, with differentiated results between treatments, indicating that the use of combined treatments and that with Metarhizium show effective results to be considered as an agroecological alternative in the control of Oebalus insularis bug.
Keywords: Metarhizium anisopliae; Oebalus insularis Stål; Oryza sativa L.; rice stink bug